Deep dry needling enhances jump performance in elite beach vlleyball players - Jiménez-Olmedo, J. M.; Grau-Aracil, A.; Penichet-Tomás, A.; Pueo, B. (Revista Internacional de Ciencias del Deporte, 2020)
The present study aims to assess whether Deep Dry Needling in latent Myofascial Trigger Points is associated with changes in jumping performance. Six Under-21 international players from the ten that belong to the national beach volleyball team received intervention in vastus lateralis and medialis of the quadriceps. Three squat jump (SJ) and countermovement jump (CMJ) trials were measured in four sessions: pre- and post-intervention (acute effect), 48 h and 7 days after intervention (long-term effects). The players showed a small decrease after the intervention followed by a non-significant increase at 48 h. However, both jump types resulted in very likely moderate increase after one week of intervention: 4.13 cm (+10.8%) and 3.54 cm (+8.9%) for SJ and CMJ, respectively (3 times the smallest worthwhile change). Despite this significant increase, the decreased performance in post-test results discourages practitioners from using this technique just before a competition.